Seismic and blast loading performance of a gypsum panelled prefabricated building - G, Gayathri; M Mini, K; S, Sruthy (International Journal of Engineering and Technology, 2018)
Urge for modern technologies and limited space leads to the idea of light weight building technology that can resist major loading condi- tions and can even be used in lands with very poor soil profile. For proper understanding of the structural response, building needs to be evaluated for natural hazards like seismic and manmade calamities like blast loading along with the normal forces acting on the structure. Whole building and structural components are also to be evaluated to study the progressive collapse of the building. This paper includes the study of static, seismic and blast loading effects on a conventional and a prefabricated building. The structural components and con- nections are also evaluated to forecast the strength of a prefabricated building using FE method. Gypsum wall panel incorporated with glass fibres and casted with cavities, as hollow and filled, are used as building panel. This study is useful in suggesting an innovative technology which is light in weight and cost effective with composite structural components.Â